Self-efficacy effect on basic level learners in speaking activities - Dewa Ayu Ari Wiryadi Joni; I Gusti Agung Putri Wirastuti (Politeknik Negeri Bali, 2018)
This study aims to reveal the effect of self-efficacy on the elementary level students and factors causing the high level of self-efficacy and its influence on students' English speaking ability. The population of this study were all students of grade VIII SMPN 3 Gianyar, while the sample of this study was taken by random sampling technique with lottery system. For research and data collection methods, the researcher uses some valid and reliable instruments, namely (1) speaking performance appraisal to know students' ability to speak English consisting of 3 criteria ie smoothness, pronunciation and improvisation, (2) self-efficacy questionnaire for knowing the high level of self-efficacy and its influence on students' speaking ability consisting of 4 components ie learning experience, field experience, social invitation, and psychological and emotional condition and analyzed with SPSS 16.0, (3) FGD guide (Focus Group Discussion) to know the factors causing the high low self-efficacy consisting of these 8 interview questions. A total of 33 students with details of 12 male and 21 female students were grouped into 3 large groups (high, medium, low) to be interviewed through FGD. The results of this study is self-efficacy gives a significant effect on students' speaking ability at the basic level of contribution of 91%. It was also found that the four criteria in self-efficacy have significant influence on students 'speaking ability, the most dominant is the criteria of students' psychic and emotional state when learning to speak English. This study contributes empirically that teachers can update their teaching techniques by observing self-efficacy in students by using creativity in teaching. In addition students can find out what happens to them during English learning so that together can create a comfortable and conducive learning atmosphere.